Dakwah Digital:: Narasi Hijrah Realistis dalam Podcast Kadam Siddik - Riska Ramadani; Tiara Nazwa Abdillah; Ari Akbar Hidayat; Wilsan; Toni Hartono (Meyarsa: Jurnal Ilmu Komunikasi dan Dakwah, 2026)
The development of digital media has created new opportunities for the dissemination of Islamic da'wah, including through podcasts that are increasingly popular among young people. This study aims to analyze digital da'wah strategies and the construction of realistic hijrah narratives in the Kadam Siddik Podcast episode Strategi Hijrah Paling Realistis (Fawaid #21). This research employs a descriptive qualitative approach with data collected through observation and documentation of podcast content. Data analysis was conducted using the Miles, Huberman, and Saldana interactive model, supported by narrative analysis and theory triangulation. The findings reveal that the Kadam Siddik Podcast constructs a realistic hijrah narrative through four integrated strategies: social environment improvement, spiritual routine formation, prayer as the foundation of istiqamah, and contextual narrative relevance to the needs of young people. These four strategies form a holistic self-transformation framework by simultaneously addressing social, behavioral, spiritual, and communicative dimensions. This narrative construction is analytically distinct from the dominant representation of instant hijrah on visual-based social media. This study concludes that podcasts serve as an effective digital da'wah medium for presenting a humanistic and contextual hijrah narrative capable of promoting sustainable spiritual transformation among the younger generation in the digital era.